Patient values and preferences on valve replacement for aortic stenosis: a systematic review. Issue 16 (9th February 2021) - Heen, Anja Fog; Lytvyn, Lyubov; Shapiro, Michael; Guyatt, Gordon Henry; Siemieniuk, Reed Alexander Cunningham; Zhang, Yuan; Manja, Veena; Vandvik, Per Olav; Agoritsas, Thomas
Abstract : The review aims to summarise evidence addressing patients' values, preferences and practical issues on deciding between transcatheter aortic valve insertion (TAVI) and surgical aortic valve replacement (SAVR) for aortic stenosis. We searched databases and grey literature until June 2020. We included studies of adults with aortic stenosis eliciting values and preferences about treatment, excluding medical management or palliative care. Qualitative findings were synthesised using thematic analysis, and quantitative findings were narratively described. Evidence certainty was assessed using CERQual (Confidence in the Evidence from Reviews of Qualitative Research) and GRADE (Grading of Recommendations Assessment, Development and Evaluation). We included eight studies. Findings ranged from low to very low certainty. Most studies only addressed TAVI. Studies addressing both TAVI and SAVR reported on factors affecting patients' decision-making along with treatment effectiveness, instead of trade-offs between procedures. Willingness to accept risk varied considerably. To improve their health status, participants were willing to accept higher mortality risk than current evidence suggests for either procedure. No study explicitly addressed valve reintervention, and one study reported variability in willingness to accept shorter duration of known effectiveness of TAVI compared with SAVR. The most common themes were desire for symptom relief and improved function. Participants preferred minimally invasive procedures with shorter hospital stay and recovery. The current body of evidence on patients' values, preferences and practical issues related to aortic stenosis management is of suboptimal rigour and reports widely disparate results regarding patients' perceptions. These findings emphasise the need for higher quality studies to inform clinical practice guidelines and the central importance of shared decision-making to individualise care fitted to each patient.